Anxiety in the Doing: Impressionist Tales of Adults Learning to be Educational Researchers - Joellen E. Coryell; M. Carolyn Clark; Susan Wagner; Carol Stuessy (Adult Education Research Conference, 2008)
This study investigated the inner experiences of adults learning to become educational researchers. Through narrative analysis of doctoral students’ tales of memorable early encounters in conducting research, insight was gained into the tension, conflict, and drama they experienced.
Keywords: doctoral programs; narrative; novice researchers